Worship and Sacrifice in Isaiah 1:10-17 A Textual Study and Application to the Contemporary Church and Society - Israel Odukogbe (European Scientific Journal, ESJ, 2020)
Worship, which includes sacrifices and offerings, has been commanded by Yahweh but not as a replacement for total obedience of the Torah. However, it is common knowledge that Israel and Judah have a long biblical history of disobedience to Yahweh. Isaiah seems to visualize a mixup of blood (bull and human), which becomes a contamination before Yahweh and in turn, rendering their sacrifices worthless. This paper examines Isaiah’s position alongside those of his contemporaries - Amos, Hosea and Micah - through a textual study - on Yahweh’s preference for obedience and social justice over empty liturgical observances. It also argues the prevalence of hypocritical services found both in Church and society today.